The fight against microbial growth "in the light" of photodynamic therapy - Bezerra, Carlos Alberto Arcelly Santos; Galdino, Fernanda Silva; Lima, Kaíque Yago Gervazio de; Martins, Giovanna Pinheiro; Nascimento, Lidiane Silva do; Gomes, Myllena Lustosa Cabral; Borchardt, Hueliton; Vasconcelos, Ulrich (Seven Editora, 2024)
With the emergence of several strains of antibiotic-resistant bacteria, there has been a demand for new therapeutic alternatives to combat the growth of microbial pathogens. PACT (Photodynamic Antimicrobial Chemotherapy) is a therapeutic modality, inspired by the treatment of tumors, that aims to kill microorganisms by photodamage, by employing the combination of a photosensitizer and light irradiation, usually of the wavelength of visible light. Thus, PACT can be applied in different contexts, with Dentistry as one of the greatest applications, but PACT can be used in the treatment of skin infections and even disinfection of surfaces in hospital and industrial environments. This paper addresses historical and technical aspects of PACT, in terms of mechanism of action, sensitive microorganisms and future perspectives. This document is the result of the final work of the discipline "Special Topics in Pharmacology II", prepared by graduate students in Natural Products, Synthetics, Bioactives, Cellular and Molecular Biology. DOI:https://doi.org/10.56238/sevened2024.010-059